Photometric and spectroscopic evolution of the interacting transient AT 2016jbu(Gaia16cfr). Issue 4 (6th May 2022) - Brennan, S J; Fraser, M; Johansson, J; Pastorello, A; Kotak, R; Stevance, H F; Chen, T -W; Eldridge, J J; Bose, S; Brown, P J; Callis, E; Cartier, R; et al.
ABSTRACT: We present the results from a high-cadence, multiwavelength observation campaign of AT 2016jbu (aka Gaia16cfr), an interacting transient. This data set complements the current literature by adding higher cadence as well as extended coverage of the light-curve evolution and late-time spectroscopic evolution. Photometric coverage reveals that AT 2016jbu underwent significant photometric variability followed by two luminous events, the latter of which reached an absolute magnitude of MV ∼ −18.5 mag. This is similar to the transient SN 2009ip whose nature is still debated. Spectra are dominated by narrow emission lines and show a blue continuum during the peak of the second event. AT 2016jbu shows signatures of a complex, non-homogeneous circumstellar material (CSM). We see slowly evolving asymmetric hydrogen line profiles, with velocities of 500 km s −1 seen in narrow emission features from a slow-moving CSM, and up to 10 000 km s −1 seen in broad absorption from some high-velocity material. Late-time spectra (∼+1 yr) show a lack of forbidden emission lines expected from a core-collapse supernova and are dominated by strong emission from H, He i, and Ca ii . Strong asymmetric emission features, a bumpy light curve, and continually evolving spectra suggest an inhibit nebular phase. We compare the evolution of H α among SN 2009ip-like transients and find possible evidence for orientation angle effects. The light-curve evolution of AT 2016jbu suggests similar, but not identical, circumstellar environments to other SN 2009ip-like transients.